A clinical case of single-stage correction of penetration combined orofacial defect with two microsurgical autografts - A. D. Kaprin; A. P. Polyakov; M. V. Ratushnyi; O. V. Matorin; M. M. Filyushin; V. N. Vasilyev; I. V. Rebrikova; A. L. Sugaipov (Опухоли головы и шеи)
After surgical treatment for locally advanced oral tumors with resection of soft tissues, mucosal membrane, and facial skeletal structures, there are penetration combined defects, removal of which is a challenge for reconstructive surgeons. Mandibular repair is one of the problems in the correction of combined oral defects. Surgeons use different grafts to remove mandibular defects. One-flap transplantation does not always solve all reconstruction problems and ensure the repair of the mucosal membrane, a soft-tissue component, skin integuments, and facial skeleton.The authors describe a clinical case of successful single-stage correction of penetration combined orofacial defect after resection of the tongue, mouth floor, en bloc resection of the lower jaw and mental soft tissues, bilateral cervical supramyochoroidal lymphadenectomy, stage LCL CM mandibular defect formation after J. Boyd, by using two microsurgical autografts (a peroneal skin-muscle-skin autograft and a radial skin-fascia one) in a 39-year-old female patient clinically diagnosed with carcinoma of the left mandibular alveolar ridge mucosa, Stage IVA (T4аN0M0).The Department of Microsurgery, P.A. Herzen Moscow Oncology Research Institute, Ministry of Health of Russia, has gained experience in comprehensively correcting extensive combined maxillofacial defects with two or more grafts in 27 patients who underwent autografting with a total of 73 flaps. The most functionally incapacitating and life-incompatible defect was removed at Stage 1 of reconstructive treatment. Delayed reconstruction was made after a complex of specialized antitumor therapy and assessment of treatment results in the absence of progressive growth. A great problem during multi-stage defect correction is presented by the lack of recipient vessels after cervical lymphadenectomy, the presence of soft tissue scar changes, trismus, temporomandibular joint ankylosis, contractures and displacement of the edges of the resected mandible, and autografting into the chronically infected area.Single-stage repair, including that using a few microsurgical autografts, is the operation of choice for adequate anatomic and functional rehabilitation, permits the promptest recovery of patients, reduces a postoperative period, and allows them to undergo an antitumor treatment cycle. However, the repair is possible, when the risk of disease progression is low, in specialized centers and when there are trained head and neck surgery and reconstructive microsurgery specialists and anesthesiologists.